Culture as Soft Power : Bridging Cultural Relations, Intellectual Cooperation, and Cultural Diplomacy - Bruno, Paula; Campanella, Lucía; Carbó-Catalan, Elisabet; Casacuberta, Margarida; Chaubet, François; Codina Solà, Núria; Dumont, Juliette; Garbisu, Margarita; Gatica Mizala, Camila; Grandjean, Martin; Humphreys, Adam; Locane, Jorge J.; et al. (2022)
This book contributes to bridge the gap between different scholarly communities interested in the entanglements of culture and politics in the international arena. It sheds light on existing connections in their parallel evolution with a thorough literature review, complemented by several case studies showing the fruitful character of their interdisciplinary mobilisation. Through the notions of cultural relations, intellectual cooperation and cultural diplomacy, the book draws on a soft power perspective to offer a shared, novel, and interdisciplinary theoretical framework to approach cultural institutions and organisations that have been previously examined as isolated objects: for example, cultural institutes, international organisations, literary magazines, and literary contests. The interdisciplinary nature of this volume justifies the relevance of its content for scholars working in the history of international relations, international cultural relations and intellectual history, comparative literature, sociology of literature and global literary studies.